The Effect of Digital Marketing, Customer Experience And Brand Equity On Customer Loyalty of Archipelago Hotels In The Special Region of Yogyakarta (DIY) - Sujoko; Dyon Tanamal; Agung Hartadi (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to analyze the influence of digital marketing, customer experience, and brand equity on customer loyalty at Hotel Archipelago in the Special Region of Yogyakarta (DIY). The research employed a purposive sampling technique, involving 130 respondents. Primary data was collected through an online questionnaire (Google Form), which was tested for validity and reliability. Data analysis included descriptive statistics, instrument testing (validity and reliability), classical assumption tests (normality, linearity, heteroscedasticity, and multicollinearity), and hypothesis testing (t-test and F-test). The coefficient of determination (R²) was used to measure the extent to which the independent variables influenced the dependent variable. Multiple linear regression analysis was conducted using IBM SPSS version 25. The results indicate that digital marketing, customer experience, and brand equity have a significant positive effect on customer loyalty. Simultaneously, these three variables also collectively exhibit a significant influence on customer loyalty at Hotel Archipelago DIY.